2021
DOI: 10.3390/ebj2040021
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Burn Patients Requiring Extracorporeal Membrane Oxygenation at a Burns Facility

Abstract: Respiratory compromise is a recognised sequelae of major burn injuries, and in rare instances requires extracorporeal membrane oxygenation (ECMO). Over a ten-year period, our hospital trust, an ECMO centre and burns facility, had five major burn patients requiring ECMO, whose burn injuries would normally be managed at trusts with higher levels of burn care. Three patients (60%) survived to hospital discharge, one (20%) died at our trust, and one patient died after repatriation. All patients required regular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…15,16 Limited evidence for ECMO use in patients with burns, in addition to few suitable patients and lack of experience, were the most commonly reported barriers to more widespread utilization of ECMO in the care of patients with severe burns. 17 A systematic review in 2013 of 69 patients found that the pooled survival of patients with severe burns and inhalation injury receiving ECMO was 54%, 18 comparable with that reported by the Extracorporeal Life Support Organization (ELSO) registry for acute respiratory failure. 19 However, more recent reports have suggested that mortality can be as high as 72%.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…15,16 Limited evidence for ECMO use in patients with burns, in addition to few suitable patients and lack of experience, were the most commonly reported barriers to more widespread utilization of ECMO in the care of patients with severe burns. 17 A systematic review in 2013 of 69 patients found that the pooled survival of patients with severe burns and inhalation injury receiving ECMO was 54%, 18 comparable with that reported by the Extracorporeal Life Support Organization (ELSO) registry for acute respiratory failure. 19 However, more recent reports have suggested that mortality can be as high as 72%.…”
Section: Introductionmentioning
confidence: 66%
“…Using it to manage patients with burns will require more specialized personnel and more man-hours than conventional therapies. 17 This study has several strengths. We used a comprehensive search strategy to effectively summarize the current literature of ECMO in burns.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation